Myosin Light Chain Kinase / Actin Interaction in Phorbol Dibutyrate-Stimulated Smooth Muscle Cells - Sean E. Thatcher; Mike E. Fultz; Hideyuki Tanaka; Haruo Hagiwara; Hou-Li Zhang; Ying Zhang; Kohichi Hayakawa; Shinji Yoshiyama; Akio Nakamura; Hong Hui Wang; Takeshi Katayama; Masaru Watanabe; et al. (Elsevier, 2011)
Abstract.: Previous work has suggested that in addition to its kinase activity, myosin light chain kinase (MLCK) exhibits non-kinase properties within its N-terminus that could influence cytoskeletal organization of smooth muscle cells (A. Nakamura et al. Biochem Biophys Res Commun. 2008;369:135-143). Myosin ATPase activity measurements indicate that the 26 - 41 peptide of MLCK significantly decreases ATPase activity as the concentration of this peptide increases. Sliding velocity of actin-filaments on myosin and stress responses in skinned smooth muscle tissue are also inhibited. Peptide-mediated uptake and the microinjection technique in cells indicate that the peptide was necessary for actin-filament stabilization. Fluorescence resonance energy transfer analysis indicated that in the presence of MLCK, α-actin but not β-actin remodeled during phorbol 12,13-dibutyrate (PDBu)-induced contractions. PDBu also induced podosomes in the cell. When MLCK expression was down-regulated by introduction of RNAi for MLCK by lentivirus vector into the cells, we failed to observe the podosome induction upon PDBu stimulation. Rescue experiments indicate that the non-kinase activity of MLCK plays an important role in maintaining actin stress fibers and in the PDBu-induced reorganization of actin-filaments in smooth muscle cells. Keywords:: actin-remodeling, podosome, phorbol 12,13-dibutyrate (PDBu), FRET analysis, myosin light chain kinase (MLCK)-deficient cell